Assessing the Relationship between Economic News Coverage and Mass Economic Attitudes. (December 2018) - Boydstun, Amber E.; Highton, Benjamin; Linn, Suzanna
Do economic performance and economic news coverage influence public perceptions of the economy? Efforts to assess the effects are hampered by the interrelationships among the variables. In this paper, we bring to bear a more careful accounting of available economic variables than previous studies have used. We find that both media tone and economic attitudes are strongly related to actual economic performance. Moreover, after taking into account the economy itself, a substantial relationship between media tone and economic attitudes persists. Given that economic attitudes influence a wide variety of political outcomes, this finding carries important normative and political significance.